Advertising self-regulation: a comparative study between the United Kingdom and Turkey, with reference to the European Union - Kural, Gülçin (My University, 2002)
Reklam özdenetimi, birçok açıdan yeni bir kavramdır. Reklam sektörü içinde aslında yıllardır varolmasına rağmen, tanıtımı ve incelenmesi konusunda yeterli bilgi bulmak zorluk yaratmaktadır. Reklam özdenetimi, bir çeşit oto kontrol olup, ondan farkının yaratıcı çalışma için daha geniş bir özgürlük alanı tanımasıdır. İngiltere ve Türkiye'de uygulanmakta olan reklam özdenetim sistemlerinin karşılaştırılması, sistemler arasındaki belirgin farklılıkları ortaya çıkarması açısından oldukça yararlı olmuştur. Bu iki sistemden bahsederken, Avrupa Birliği'ne referans vermek gereklidir. Yapılan karşılaştırma sırasında, İngiltere'nin reklam özdenetim sisteminin dünyadaki ilk örneklerden biri olduğu, bu nedenle de Türkiye'deki sistemden çok daha köklü ve deneyimli bir yapıya sahip olduğu anlaşılmıştır. Bu araştırmanın sonunda, reklam özdenetimi konusunda daha fazla çalışma yapılmasının, bu konuda geniş bir kaynak oluşturması açısından gerekli olduğu görülmektedir. The aim to prepare this thesis on advertising self-regulation is that the idea and the improvements on this issue are rather new. Advertising self-regulation is a kind of auto control system, different from the origin, it provides more freedom for the creator or the advertisement. The comparison between the self-regulatory systems of the United Kingdom and Turkey is chosen to point out the differences and the common ground of these two countries' understanding of the self-regulation in advertising sector. The European Union is among the common points of these two countries and it is required to make certain references. As a conclusion, there are particular differences between the United Kingdom and Turkey, such as the establishment of the self-regulation in advertising is rather new in Turkey, while it has a relatively old past in the UK. It is very well understood that there is a need to have more of researches on the advertising self-regulation in the purpose of providing more sources on this issue.
Keywords: Reklamcılık